Gamma Delta T Cells: A Prospective Analysis of Their Regeneration Kinetics and Their Impact on the Clinical Outcome Following Allogeneic Hematopoietic Stem Cell Transplantation - Eida Elmansorry (AlQalam Journal of Medical and Applied Sciences, 2024)
Haematopoietic stem cell transplantation (HSCT) plays an important role in the therapy of hematological malignancies. Gamma delta T cells (ᵞᵟ T cells) are a distinct lineage of T lymphocytes that might play an important role in immune recovery and could utilize a graft –versus –leukemia effect post HSCT, furthermore, higher counts of ᵞᵟ T cells could improve clinical outcome after HSCT. This work was conducted to analyze the kinetics of gamma delta T cells recovery post HSCT, and to correlate their reconstitution with different factors that may influence the clinical outcome following HSCT. In this study, 22 consecutive allogeneic hematopoietic stem cell transplantation (HSCT) recipients were analysed during the first-year post transplantation by measuring the absolute count of CD3 T cells and percentages of gamma delta T cells subsets every month for each patient using flow cytometric technique. Statistics (means, minimal, and maximal values) were used to describe patient baseline characteristics. Results were presented as mean values of CD3+, gamma delta T cells %, and p-values. Higher gamma delta T cells percentages were significantly correlated with younger patient and donor age, sex matched transplantation, leukemic diseases, un-manipulated transplants, and in patients without chronic graft versus host disease complications. Furthermore, positive correlation between CD3 T cells counts and gamma delta T cells % was also determined. Overall survival and better clinical outcome following allogeneic HSCT could be related with proper gamma delta T cells reconstitution. زراعة الخلية الجذعية الدموية تلعب دورا اساسيا في علاج الامراض السرطانية التي تصيب الدم. الخلايا الليمفاوية من نوع جاما- دلتا وهي نوع متميز من الخلايا الليمفاوية التائية التي لها دور في اعادة تشكل المناعة بعد الزراعة ,كما ان لها دورا في القضاء على الخلايا السرطانية التي قد تنشط بعد الزراعة بمعنى اخر ان زيادة عدد خلايا جاما-دلتا ,قد يرافقها تحسن الحالة السريرية للمرضى بعد الزراعة. هدف البحث: تم اجراء هذا البحث لتحليل الية تطور خلايا جاما-دلتا بعد الزراعة, و ربط تطورها بالعديد من العوامل التي قد تؤثر على الحالة السريرية للمرضى بعد الزراعة. تم تحليل عينات من 22 مستقبلا لزراعة الخلية الجذعية الدموية خلال العام الاول من الزراعة, وذلك بقياس العدد المطلق للخلايا التائية الحاملة للمستقبل سي دي 3 وكذلك نسبة خلايا جاما-دلتا كل شهر باستعمال طريقة التدفق الخلوي وتحديد المتوسط, القيمة الاعلى والقيمة الادنى. وجدنا ان النسبة المرتفعة لخلايا جاما- دلتا ترتبط مع العمر الصغير للمريض والمتبرع, وكذلك عند تطابق الجنسين بين المتبرع والمستقبل, وفي مرض سرطان الدم الابيضاضي, وفي الزراعة غير المعالجة, وكذلك عند المرضى بدون المضاعفات الناتجة عن تفاعل الخلايا المزروعة مع خلايا المستقبل النوع المزمن, وبالإضافة الىى ذ لك تم ايجاد علاقة ايجابية بين نسبة خلايا جاما- دلتا وعدد الخلايا التائية الحاملة للمستقبل سي دي 3. بشكل عام, القدرة على البقاء وتحسن الحالة السريرية للمرضى بعد زراعة الخلايا الجذعية الدموية له علاقة بتحسن اعادة تشكل خلايا جاما-دلتا بعد الزراعة